THE ANALYSIS OF CONSUMER PURCHASE INTENTION TOWARDS COSMETIC PRODUCTS BASED ON PRODUCT ORIGIN - Sulu, Anastasia Cherry; Saerang, David P. E.; Massie, James D. D. (Universitas Sam Ratulangi, 2016)
In this modern era, the use of cosmetic products has become the things that are important starting from infancy to old age. Then consumers offered with so many different kinds of cosmetic products, which come from different brands. In order to have, beautiful skin, healthy hair and good-looking appearance. The objectives of this research are to identify which country–of–origin people prefer the most for cosmetic products and to identify which criterion is the most influential in selecting cosmetic products. To accomplished the objectives, data were collected in Manado through questionnaire. This quantitative descriptive research was using Analytical Hierarchy Process. Sample size is 60 women who have intention to buy cosmetic products. As the result of this research, the United States cosmetic products is the most preferred country–of–origin by the consumer since United States always has the biggest score, followed by South Korea and Indonesia. Based on overall result, price is the most preferred among six criteria for selecting cosmetic products followed consecutively by brand, promotion, quality, packaging and the last is availability. This research suggests, South Korea and Indonesia need to improve the performance considering the criteria that have been analyzed. Then among the criteria, price has important role so retailers and producers have to pay more attention toward this factor. Keywords: consumer purchase intention, country–of–origin, analytical hierarchy process